Cerebrospinal fluid acid-base status and lactate and pyruvate concentrations after short (less than 30 minutes) first febrile convulsions in children. Issue 11 (November 1977) - Simpson, H; Habel, A H; George, E L
Abstract : Twenty-nine infants and children with short (less than 30 minutes) first febrile convulsions were studied between 3 and 22 hours after convulsive episodes. Arterial and CSF acid-base variables, lactate and pyruvate concentrations, and lactate/pyruvate ratios were measured. Biochemical signs of cerebral hypoxia were found in only 2 patients, one of whom had short, repeated convulsions. Our findings indicate that hypoxic damage is unlikely to result from a short-duration febrile convulsion.